Elevated liver transaminase levels prolong hospital stay in dengue patients: retrospective cohort study - Alnweiri, Abdelrahman MS; Prihartono, Nurhayati A. (BKM Public Health and Community Medicine, 2025)
Purpose: To evaluate the public health impact of elevated liver transaminases (AST/ALT >35 U/L) on hospitalization duration in adult dengue patients in Indonesia’s resource-constrained settings. Methods: Retrospective cohort study of 786 confirmed dengue patients at Ummi Hospital, Bogor (2021–2023). We analyzed demographics, comorbidities, hepatoprotective therapy, and AST/ALT levels. Prolonged stay was defined as ≥5 days. Multivariate logistic regression identified predictors of prolonged length of stay (LOS). Results: 41.9% had elevated transaminases. Patients with enzyme elevations had longer hospital stays than those with normal levels. Non-comorbid patients with elevated enzymes were significantly more likely to experience prolonged hospitalization. Comorbidities markedly increased the risk of extended stays, while hepatoprotective therapy reduced it. Nationally, this could save ~105,000 bed-days annually. Conclusion: Elevated transaminases independently predict prolonged dengue hospitalization. Routine liver monitoring and hepatoprotective therapy may optimize bed utilization in Indonesian hospitals.